General and Toxicologic Aspects of Occupational Fatalities in the Metropolitan Area of Lyon From 2000 to 2020, a Retrospective Study - Lamouroux, Céline; Pouliquen, Guillaume; Fort, Emmanuel; Epain, Marie; Marfaing, Florent; Charbotel, Barbara; Fanton, Laurent (La Medicina del Lavoro, 2026)
Over the past two decades, fatal workplace accidents have accounted for between 300,000 and 400,000 deaths a year worldwide. The aim of this study was to investigate the general characteristics and the toxicological profile of work-related deaths. A descriptive retrospective study was carried out on occupational-related deaths occurred in the Lyon metropolitan area from 2000 to 2020 from the autopsy reports of the University Institute of Legal Medicine. A total of 476 cases of work-related deaths were identified, of which 91% were men. The median age was 48 years, 44% of the deaths were due to cardiac origin, 34% to mechanical accidents and 18% to suicide. 16 homicides were also recorded. The cause of death differed significantly between socio-professional categories: suicide was the main cause of death among managers & intellectual occupations (50%), cardiovascular death among non-manual elementary workers (53%), manual elementary workers (49%) and craftsmen, shop keepers & business owners (33%), and physical accidents among farmers (50%) and manual elementary workers (48%). The main cause of death varied by sector: physical accidents in construction (61%), cardiovascular events in transportation and storage (67%) and manufacturing (51%). 27% (n = 130) tested positive for at least one psychoactive substance, including 75 for alcohol, 43 for sedative anxiolytics and 33 for cannabis. These results may help occupational health professionals to design policies and campaigns to prevent deaths among the workers concerned. Specific studies to assess the proportion of fatal accidents attributable to the use of alcohol, cannabis or benzodiazepines could contribute to reducing work-related deaths.